2019
DOI: 10.1042/bcj20180828
|View full text |Cite
|
Sign up to set email alerts
|

Structure of SPH (self-incompatibility protein homologue) proteins: a widespread family of small, highly stable, secreted proteins

Abstract: SPH (self-incompatibility protein homologue) proteins are a large family of small, disulfide-bonded, secreted proteins, initially found in the self-incompatibility response in the field poppy (Papaver rhoeas), but now known to be widely distributed in plants, many containing multiple members of this protein family. Using the Origami strain of Escherichia coli, we expressed one member of this family, SPH15 from Arabidopsis thaliana, as a folded thioredoxin fusion protein and purified it from the cytosol. The fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 51 publications
(102 reference statements)
1
22
0
Order By: Relevance
“…Based on the large number of SPH family members, all encoding proteins with signal peptides, together with their wide distribution, it has previously been proposed that they may be ligands involved in a wide range of signaling pathways (Ride et al, 1999). It has been suggested that this family of proteins may have evolved to act as a versatile and stable scaffold to display a variety of peptides in the predicted extracellular loops, each interacting with a different receptor (Rajasekar et al, 2019). Our findings here, showing that PrsS can trigger responses in vegetative tissues, provide further hints that (depending on how they have evolved) perhaps other SPHs may be involved in signaling in different tissues.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Based on the large number of SPH family members, all encoding proteins with signal peptides, together with their wide distribution, it has previously been proposed that they may be ligands involved in a wide range of signaling pathways (Ride et al, 1999). It has been suggested that this family of proteins may have evolved to act as a versatile and stable scaffold to display a variety of peptides in the predicted extracellular loops, each interacting with a different receptor (Rajasekar et al, 2019). Our findings here, showing that PrsS can trigger responses in vegetative tissues, provide further hints that (depending on how they have evolved) perhaps other SPHs may be involved in signaling in different tissues.…”
Section: Discussionmentioning
confidence: 51%
“…Our data showing that the PrpS-PrsS module can act ectopically provide potential new clues to the possible origin and evolution of bipartite genetic modules that act in cell-cell signaling networks. PrsS has homologs in a large family named after them, the SPHs (also known as plant self-incompatibility protein S1 homologs in the databases), comprising more than 1,800 homologous sequences in more than 70 plant species as well as in fungi and metazoa (Ride et al, 1999;Rajasekar et al, 2019). Over 90 SPHs have been identified in Arabidopsis (Rajasekar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations